Tantangan Dan Solusi Penerimaan Mahasiswa Baru Prodi Filsafat Hindu Stahn Mpu Kuturan Singaraja - Hartaka, I Made; Eka Suadnyana, Ida Bagus Putu; Somawati, Ayu Veronika (LPM IHDN Denpasar, 2021)
The quantity of students for a college is of particular concern, this is because the quantity of students indirectly affects public confidence in educational institutions. In addition, the quantity of students will also affect the assessment process of the institution by the competent body or institution. So that the quantity of students is always strived to increase every year both by universities and study programs as a unit of education in it. The selection of a study program is not a question that can be decided simply. There are many determinants that prospective students should consider. From various searches of literary sources, it was found that the factor that determines the basis for choosing is attraction or attractiveness.In addition, a person's decision to make a choice often occurs very quickly sometimes less than half a minute and is influenced by the likes and beliefs.The study program in attracting prospective students must conduct study and analysis as a first step.Looking at what are the strengths, weaknesses, opportunities and challenges that may arise today, this of course becomes important because the results of this study can affect in the process of achieving organizational goals, especially in an effort to increase the number of students.Â